Precision medicine: a new era for inner ear diseases - Tavazzani, Elisa; Spaiardi, Paolo; Contini, Donatella; Sancini, Giulio; Russo, Giancarlo; Masetto, Sergio (Frontiers in Pharmacology, 2024)
The inner ear is the organ responsible for hearing and balance. Inner ear dysfunction can be the result of infection, trauma, ototoxic drugs, genetic mutation or predisposition. Often, like for Ménière disease, the cause is unknown. Due to the complex access to the inner ear as a fluidfilled cavity within the temporal bone of the skull, effective diagnosis of inner ear pathologies and targeted drug delivery pose significant challenges. Samples of inner ear fluids can only be collected during surgery because the available procedures damage the tiny and fragile structures of the inner ear. Concerning drug administration, the final dose, kinetics, and targets cannot be controlled. Overcoming these limitations is crucial for successful inner ear precision medicine. Recently, notable advancements in microneedle technologies offer the potential for safe sampling of inner ear fluids and local treatment. Ultrasharp microneedles can reach the inner ear fluids with minimal damage to the organ, collect ul amounts of perilymph, and deliver therapeutic agents in loco. This review highlights the potential of ultrasharp microneedles, combined with nano vectors and gene therapy, to effectively treat inner ear diseases of different etiology on an individual basis. Though further research is necessary to translate these innovative approaches into clinical practice, these technologies may represent a true breakthrough in the clinical approach to inner ear diseases, ushering in a new era of personalized medicine.